2020
DOI: 10.1093/nar/gkaa225
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the paradoxical mechanical response of in-phase A-tracts at different force regimes

Abstract: A-tracts are A:T rich DNA sequences that exhibit unique structural and mechanical properties associated with several functions in vivo. The crystallographic structure of A-tracts has been well characterized. However, the mechanical properties of these sequences is controversial and their response to force remains unexplored. Here, we rationalize the mechanical properties of in-phase A-tracts present in the Caenorhabditis elegans genome over a wide range of external forces, using single-molecule experiments and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 83 publications
7
56
0
Order By: Relevance
“…6), so local bends can couple for building up a significant curvature. Our results are in the same line of others that highlighted the importance of periodicity 32,72,73 for understanding the special mechanical properties of A-tracts 19 or nucleosome-positioning sequences. [74][75][76] Protein-DNA and sequence mismatch SerraNA has the capacity to deal with perturbed DNA molecules caused by a series of factors like sequence mismatch or protein binding.…”
Section: Stretch Modulussupporting
confidence: 92%
See 1 more Smart Citation
“…6), so local bends can couple for building up a significant curvature. Our results are in the same line of others that highlighted the importance of periodicity 32,72,73 for understanding the special mechanical properties of A-tracts 19 or nucleosome-positioning sequences. [74][75][76] Protein-DNA and sequence mismatch SerraNA has the capacity to deal with perturbed DNA molecules caused by a series of factors like sequence mismatch or protein binding.…”
Section: Stretch Modulussupporting
confidence: 92%
“…16,17 In addition, it has been very difficult to identify the mechanisms through which some short sequence motifs, like A-tracts, originate extraordinary bending. 18,19 On these matters, molecular dynamics (MD) simulations at atomic resolution have become an impressive source of new important information, 20 that have provided (i) systematic analysis at the dinucleotide level, 21,22 (ii) an evaluation of the influence of nearest flanking base-pairs (bp) up to the tetranucleotide level 23,24 and, among others, (iii) an explanation of contradictory stiffness data on A-tracts. 25 On a more coarse-grained level, Monte Carlo (MC) simulations have found that most of sequence-dependence variability is originated at the level of static curvature.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the presence of intrinsic bending, our AU-tracts also presented significant deviations from the WLC in the data. Moreover, the shape of the plot for the phased AU-tract studied here is remarkably similar to an intrinsically-bent A-tract dsDNA that we recently reported (24). Finally, we checked whether the AU-tracts caused anomalous migration of dsRNA in agarose gels, as occurs for A-tracts in dsDNA molecules.…”
Section: Au-tracts: Similarities and Differences With Dna A-tractssupporting
confidence: 78%
“…Further analysis of our data in terms of the cosines of the tangents provided a more stringent test to the WLC model (24) (39). For the control molecule, the cosines of the tangents reasonably fitted to the WLC model (Eq.…”
mentioning
confidence: 86%
See 1 more Smart Citation